2009
DOI: 10.2353/ajpath.2009.080476
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory and Renal Protective Actions of Stanniocalcin-1 in a Model of Anti-Glomerular Basement Membrane Glomerulonephritis

Abstract: We have previously shown that stanniocalcin-1 (STC1) inhibits the transendothelial migration of macrophages and T cells, suppresses superoxide generation in macrophages, and attenuates macrophage responses to chemoattractants. To study the effects of STC1 on inflammation, in this study we induced a macrophage-and T-cell-mediated model of anti-glomerular basement membrane disease in STC1 transgenic mice, which display elevated serum STC1 levels and preferentially express STC1 in both endothelial cells and macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 62 publications
1
63
0
1
Order By: Relevance
“…There were higher levels of expression of the antiinflammatory protein TSG-6 than previously observed by preincubation of hMSCs with TNFα (14). Also, there was a high level of expression of STC-1, a protein with both antiinflammatory and antiapoptotic effects (13,29). The high levels of expression of both TSG-6 and STC-1 were maintained for at least 1 d after the cells were dissociated from the spheroids.…”
Section: Discussionmentioning
confidence: 78%
“…There were higher levels of expression of the antiinflammatory protein TSG-6 than previously observed by preincubation of hMSCs with TNFα (14). Also, there was a high level of expression of STC-1, a protein with both antiinflammatory and antiapoptotic effects (13,29). The high levels of expression of both TSG-6 and STC-1 were maintained for at least 1 d after the cells were dissociated from the spheroids.…”
Section: Discussionmentioning
confidence: 78%
“…However, this issue should be revisited by expanded analyses of various subsets of additional tumor stromal cells, such as fibroblasts, pericytes, and neutrophils. These future analyses should also consider recent studies, which have implicated STC1, in noncancer models, as a regulator of inflammation, macrophage mobility, and vascular permeability (39)(40)(41)(42). Interestingly, earlier studies have also shown that hypoxia, a prometastatic stimuli, also leads to the upregulation of STC1 (43).…”
Section: Discussionmentioning
confidence: 88%
“…STC1 Tg is driven by the metallothionein I minimal promoter over C57B/6 genetic background, 27 and their phenotype has been described in previous studies. 16,27,50 SIRT3 Tg is driven by the cytomegalovirus early enhancer/chicken actin promoter on C57B/6 background; mice display no overt phenotype (unpublished data). STC1 KO and STC1/STC2 double KO are also on C57B/6 genetic background and have been described elsewhere.…”
Section: Micementioning
confidence: 97%